Yb-doped passively mode-locked fiber laser with Bi2Te3-deposited*Project supported by the National Natural Science Foundation of China (Grant No. 61378024) and the Natural Science Fund of Guangdong Province, China (Grant No. S2013010012235). (20th October 2015) - Li 李, Lu 璐; Yan 闫, Pei-Guang 培光; Wang 王, Yong-Gang 勇刚; Duan 段, Li-Na 利娜; Sun 孙, Hang 航; Si 司, Jin-Hai 金海
Abstract: In this study we present an all-normal-dispersion Yb-doped fiber laser passively mode-locked with topological insulator (Bi2 Te3 ) saturable absorber. The saturable absorber device is fabricated by depositing Bi2 Te3 on a tapered fiber through using pulsed laser deposition (PLD) technology, which can give rise to less non-saturable losses than most of the solution processing methods. Owing to the long interaction length, Bi2 Te3 is not exposed to high optical power, which allows the saturable absorber device to work in a high power regime. The modulation depth of this kind of saturable absorber is measured to be 10%. By combining the saturable absorber device with Yb-doped fiber laser, a mode-locked pulse operating at a repetition rate of 19.8 MHz is achieved. The 3-dB spectral width and pulse duration are measured to be 1.245 nm and 317 ps, respectively.